CROP PRODUCTIVITY OF SPRING BARLEY VARIETY DOKUCHAYEVSKYI 15 DEPENDING UPON APPLICATION OF DIFFERENT SEEDING RATES AND FOLIAR ADDITIONAL FERTILIZING - Рожков, А. О.; Чернобай, С. В. (Scientific Progress & Innovations, 2014)
The results of the researches conducted during 2012-2014 on the experimental field of KhNAU named after V. V. Dokuchayev concerning the influence of application of different variants of seeding rates and crops foliar additional fertilizing with complex fertilizers and biological preparations on the variability of spring barley crops productivity variety Dokuchayevskyi 15 are given in the article. During the researches it was established the optimum seeding rate for the studied spring barley variety – 5,0 million/ha which provides the highest crops grain productivity formation. The high efficiency of complex application of Crystalon special with biopreparation agro EM was defined. Crops grain productivity on this variant increased from 2,31 ​​to 2,43 t/ha in comparison with the control. During the analysis the degree of connection between crops grain productivity and yield structure main elements was determined.